The association between dietary creatine intake and cancer in U.S. adults: insights from NHANES 2007–2018 - Jiang, Junhui; Zhao, Hu; Chen, Jiong; Du, Junhao; Ni, Weixiang; Zheng, Baohua; Wu, Junhong; Xiao, Chunhong (Frontiers in Nutrition, 2025)
BackgroundCreatine has anti-inflammatory, antioxidant, and immunomodulatory effects. However, its impact on tumors remains uncertain.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018 to investigate the relationship between dietary creatine intake and cancer in American adults. A total of 25,879 participants aged 20 years and older were included, and their medical information, dietary creatine intake, and covariates were collected. Multiple logistic regression models were used to assess the relationships between age, dietary creatine intake, and cancer risk. Restricted cubic spline (RCS) analysis explored the nonlinear relationships between dietary creatine intake, age, and cancer prevalence.ResultsRCS analysis revealed a linear, negative association between dietary creatine intake and cancer risk. For each standard deviation (SD) increase in dietary creatine intake, cancer risk decreased by 5% (adjusted odds ratio (OR) = 0.95, 95% CI: 0.91–0.99, p = 0.025). This negative association was strongest among males (adjusted OR = 0.93, 95% CI: 0.88–0.99, p = 0.021) and overweight participants (adjusted OR = 0.92, 95% CI: 0.84–0.99, p = 0.044). Interaction results indicated specific age group effects. Further analysis showed that higher dietary creatine intake was significantly inversely associated with cancer risk among older adults (adjusted OR = 0.86, 95% CI: 0.77–0.97, p = 0.014). RCS analysis revealed a linear, positive correlation between age and cancer risk. For each SD increase in age, cancer risk increased by 3.27 times (adjusted OR = 3.27, 95% CI: 3.07–3.48, p < 0.001).ConclusionThese findings suggest that higher dietary creatine intake may reduce cancer risk in a nationally representative adult population. Further prospective studies are needed to clarify the relationship between dietary creatine intake and cancer risk.